Mechanical, thermal, morphological and flammability properties of halloysite nanotube reinforced compatibilized poly(ethylene terephthalate) / polypropylene nanocomosities [electronic resource] - Noorzilawani Che Abdul Razak, 1987-, author 602558; Azman Hassan, supervisor 342780; Sani Amril Samsudin; Fakulti Kejuruteraan Kimia dan Kejuruteraan Tenaga 599090 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Kejuruteraan (Polimer))